2015
DOI: 10.1016/j.virol.2014.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the molecular manipulation of DCAF1 by the lentiviral accessory proteins Vpr and Vpx

Abstract: Vpr and Vpx are primate lentivirus proteins that manipulate the cellular CRL4 ubiquitin ligase complex. While Vpr is common to all primate lentiviruses, Vpx is only encoded by HIV-2 and a limited range of SIVs. Although Vpr and Vpx share a high degree of homology they are known to induce markedly different effects in host cell biology through the recruitment of different substrates to CRL4. Here we explore the interaction of HIV-1 Vpr and SIVmac Vpx with the CRL4 substrate receptor DCAF1. Through mutational an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Comparing with human ( Homo sapiens [ Hs ]) DCAF1, Drosophila melanogaster ( Dm ) Mahj also contains a LisH motif, a helix-loop-helix (HLH) motif, a WD40 domain, and an acidic domain (Fig 4B). The LisH motif of Hs DCAF1 is responsible for the dimerization of DCAF1 [37], whereas the HLH motif and WD40 domain are important for the binding of DCAF1 to DDB1 [3840]. From our homology model of the Dm Mahj- Dm DDB1 complex, which was generated from the published crystal structure of the Hs DCAF1- Hs DDB1 complex (Protein Data Bank [PDB] 5JK7 [39]), Mahj likely uses its HLH motif and WD40 domain to interact with DDB1 (S4A–S4C Fig).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing with human ( Homo sapiens [ Hs ]) DCAF1, Drosophila melanogaster ( Dm ) Mahj also contains a LisH motif, a helix-loop-helix (HLH) motif, a WD40 domain, and an acidic domain (Fig 4B). The LisH motif of Hs DCAF1 is responsible for the dimerization of DCAF1 [37], whereas the HLH motif and WD40 domain are important for the binding of DCAF1 to DDB1 [3840]. From our homology model of the Dm Mahj- Dm DDB1 complex, which was generated from the published crystal structure of the Hs DCAF1- Hs DDB1 complex (Protein Data Bank [PDB] 5JK7 [39]), Mahj likely uses its HLH motif and WD40 domain to interact with DDB1 (S4A–S4C Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Besides binding to Hs DDB1, the WD40 domain of Hs DCAF1 is also critical for interaction with substrates [38,40]. Therefore, we explored whether the WD40 domain of Mahj mediated its interaction with Wts.…”
Section: Resultsmentioning
confidence: 99%
“…Vpr has two widely studied activities: one is its ability to induce G 2 cell cycle arrest, and the other is to increase HIV-1 replication in macrophages (32, 33). The molecular mechanism of G 2 arrest induction by Vpr has been attributed to a number of host target proteins (34, 35). In one report, Vpr is found to target MUS81 for degradation through the CRL4 VprBP E3 ligase, resulting in premature activation of the SLX4 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that DCAF1 fragments overlapping the WD40 motif can associate with DDB1 (Le Rouzic et al, 2008; McCall et al, 2008; Cassiday et al, 2015). However, a minimal fragment containing only the residues comprising the seven-bladed β-propeller motif of DCAF1 fails to bind DDB1, suggesting another interface helps stabilize the interaction with DDB1 (Cassiday et al, 2015). DDB1 itself is comprised of three WD40 β-propeller domains (designated BPA, BPB, and BPC) which adopt a planar, three-bladed conformation.…”
Section: Domain Organization Of Dcaf1 and Structural Characterizationmentioning
confidence: 99%